Evaluasi Pemanfaatan Sarana dan Prasarana di sekolah - Rangga Hasibuan; Zahra Nabila Iqbal; Sari Andini; Abdul Fattah Nasution (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
School facilities are fundamental for achieving an effective, efficient, and character-building learning environment . SMP IT Al-Hijrah, accredited A school, provides facilities such classrooms, a computer lab, prayer room, and reading room, proactively managed by the Vice Principal for Facilities. This study aims to evaluate the adequacy and accessibility of facilities, facility management, and integration of infrastructure into the learning process and character development of students at SMP IT Al Hijrah. Utilizing a descriptive qualitative approach through observation, in-depth interviews with the Vice Principal for Facilities, Data analysis was conducted through reduction, thematic presentation. Results show that the school’s facilities are adequate and accessible, management is systematic and sustainable, and infrastructure integration supports student motivation as well as religious and environmental character formation. Facility management and utilization at SMP IT Al-Hijrah successfully create a synergy between physical quality, systematic administration, and a character-based learning environment. It is recommended to maintain the established management procedures and further develop the facilities.